The effect depression levels in midwives have on burnout and their level of job satisfaction - Altiparmak, Sumeyye; Yilmaz, Ayse N. (European Publishing, 2021)
INTRODUCTION This study aimed to determine the effect of depression levels in midwives on burnout and job satisfaction. METHODS The sample of this descriptive study consisted of 322 midwives working in a province located in the eastern region of Turkey. Data were collected by using the Personal Information Form, Beck Depression Inventory (BDI), Maslach Burnout Inventory (MBI), and Minnesota Job Satisfaction Questionnaire (MJSQ) Short Form. RESULTS The rate of midwives experiencing depression was found to be 9.6%. The mean score of MJSQ was 64.59 +/- 13.29, while the mean scores for the sub-dimensions of MBI were: emotional burnout 18.57 +/- 6.65, decrease in sense of personal accomplishment 21.65 +/- 3.93, and depersonalization 6.25 +/- 3.86. It was found that midwives who did not experience depression (90.4%) had a higher level of job satisfaction and a higher sense of personal accomplishment (p<0.05). On the other hand, midwives experiencing depression (9.6%) had higher levels of emotional exhaustion and depersonalization. It was found that there was a negative weak relationship between BDI and job satisfaction and personal accomplishment, and a positive weak relationship between BDI and emotional exhaustion (p<0.05). CONCLUSIONS It was determined that midwives with depression have lower levels of job satisfaction and personal success, and experience emotional exhaustion more frequently. In addition, it was observed that as the level of depression decreased, job satisfaction and personal success increased significantly, whereas emotional exhaustion decreased.
Keywords: depression; emotional exhaustion; midwife; job satisfaction; exhaustion